A correlation study of happiness, motivation and stress from creative pursuits. - Krishna Kumar, V. (London : SAGE Publications, Ltd., 2023)
V. Krishna Kumar, PhD, professor emeritus, Westchester University, discusses a correlation study of happiness, motivation and stress from creative pursuits, including research design, recruitment, ethical considerations, data collection and analysis, research findings, challenges faced, and lessons learned.
Includes bibliographical references and index.
Academic, V. Krishna Kumar PhD.
Closed-captioned in English.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Creative ability -- Psychological aspects; Happiness; Motivation (Psychology); Stress (Psychology)